Gender earnings differentials and regional economic development in urban China, 1988 - 97 - Ying Chu Ng (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Gender earnings differentials in urban China by region and their changes during the first decade of economic reform are examined. It is found that the female–male earnings ratio increased during the early stage of reform. The male earnings premium, overall, showed an increasing trend in the later stage of reform. Decomposition of the gender earnings differential reveals that a relatively lower percentage of the differential could be explained by gender differences in productive characteristics in the fast growing regions and in regions with a rapid pace of reform. The cross-sectional results highlight the possible existence of gender discrimination, particularly in the later stages of economic reform and development. Both market competition and the effects of wage decentralization play a role in shaping the gender earnings differentials. Gender earnings differentials varied by region and over time, generally in tandem with the pace of economic reform and development. The decomposition of the over time changes in the earnings gap indicated that improvement in females' productive characteristics during the reform period constantly enhanced the earnings of females relative to those of males. The over time changes in the returns to females' characteristics, however, work to counter any narrowing of the gender earnings gap.
Keywords: J7; J3; O0; 330; gender earnings differentials; urban China; transitional economies; Lohnstruktur; Geschlecht; Stadtentwicklung; China